LPS‐induced systemic inflammation is more severe in P2Y12 null mice. Issue 2 (18th October 2013) - Liverani, Elisabetta; Rico, Mario C.; Yaratha, Laxmikausthubha; Tsygankov, Alexander Y.; Kilpatrick, Laurie E.; Kunapuli, Satya P.
Abstract : Inflammatory responses in LPS‐induced systemic inflammation are increased in P2Y12 null mice. Abstract : Thienopyridines are a class of antiplatelet drugs that are metabolized in the liver to several metabolites, of which only one active metabolite can irreversibly antagonize the platelet P2Y12 receptor. Possible effects of these drugs and the role of activated platelets in inflammatory responses have also been investigated in a variety of animal models, demonstrating that thienopyridines could alter inflammation. However, it is not clear whether it is caused only by the P2Y12 antagonism or whether off‐target effects of other metabolites also intervene. To address this question, we investigated P2Y12 KO mice during a LPS‐induced model of systemic inflammation, and we treated these KO mice with a thienopyridine drug (clopidogrel). Contrary to the reported effects of clopidogrel, numbers of circulating WBCs and plasma levels of cytokines were increased in LPS‐exposed KO mice compared with WT in this inflammation model. Moreover, both spleen and bone marrow show an increase in cell content, suggesting a role for P2Y12 in regulation of bone marrow and spleen cellular composition. Finally, the injury was more severe in the lungs of KO mice compared with WT. Interestingly, clopidogrel treatments also exerted protective effects in KO mice, suggesting off‐target effects for this drug. In conclusion, the P2Y12 receptor plays an important role during LPS‐induced inflammation, and this signaling pathway may be involved in regulating cell content in spleen and bone marrow during LPS systemic inflammation. Furthermore, clopidogrel may have effects that are independent of P2Y12 receptor blockade.